Reliving the moments: Exploring tourists’ staycation experience through S-O-R framework - Pratminingsih, Sri Astuti; Zulganef , Zulganef; Purwaningdyah, Sri Wiludjeng Sunu (Jurnal Siasat Bisnis, 2024)
Purpose – The purpose of this study is to understand what influences tourists’ travel experience sharing and intention to re-staycation. S-O-R framework is used to examine how social influence affects perceived enjoyment, while subsequently sharing their staycation experience and intention to re-staycation. Design/methodology/approach – 325 generation Z millennials who have experienced staycation and share it to their social media are chosen using purposive sampling. The data obtained is processed using Structural Equation Modeling with AMOS.Findings – The findings of this study indicate that social influence affects tourists’ perceived enjoyment on staycation trip, which then leads to staycation experience sharing and tourists’ intention to re-staycation. Experience sharing mediates the influence of perceived enjoyment on staycation trip towards intention to re-staycation. Review credibility and gender differences moderate the relationships between variables.Research limitations/implications – This study has not yet look at the post-travel or staycation phase of tourists, thus further study is needed regarding post-travel evaluation. It also only uses variables that focus on tourists' perspectives regarding their travel experiences and sharing activities on social media.Practical implications – Service providers must pay attention to improving the atmosphere not only in terms of physical attributes but also related to the service products available in the hotel so that it can attract the intention to visit again. Offering accommodation experiences can enable potential tourists to return to the destination.Originality/value – Through the SOR framework, this study show how social influence can be a stimulus for individuals in perceiving enjoyment during their trip, leading them to show a behavioral response of sharing their staycation experience and have intention to go back to relive the moments.